Metode Super Tahfidz Sebagai Upaya Peningkatan Hafalan Juz Amma Anak - Siti Makhmudah (ANNAHDLIYAH: Jurnal Manajemen Pendidikan Islam, 2025)
The aims of this study is. Describe efforts to improve juz amma memorization through super tahfidz method. Know the prototype of juz amma memorization for children through super tahfidz method. Know the level of validity and practice for efforts to improve juz amma memorization through super method. tahfidz in Arrahman Kindergarten Kertosono. Type of research: a type of research and development (Research and development). The results showed that efforts to increase juz amma memorization through super tahfidz methods in Arrahman Kertosono Kindergarten can be illustrated by the lack of understanding of educators, especially teachers and students about the use of juz amma memorization methods in kindergarten children. A description of the efforts Improvement of memorization of juz amma in children using the super tahfidz method consists of two components namely the philosophy component of the model and the component implementation of the model. While the operational components of the model are detailed in all types of methods used. All activities are packaged with the aim to improve children's memorization through the super tahfidz method. The level of content validity and practicality of improving juvenile juz memorization through the super tahfidz method shows that the validator's assessment of all devices that have been presented can be declared valid for use in efforts to improve memorization children through the super tahfidz method, fulfill the practical aspects so that it is appropriate to use.